Od arhitekturnega konzervatorstva, obnove in prenove do integralnega varstva dediščine - Lah, Ljubo (Urbani izziv, 2001)
Problems with heritage protection already begin with its defeinition. Aspects that are widening the present understanding of heritage are increasingly gaining in recognition. Its real meaning is repeatedly redefined only by evaluation. An integral part of heritage protection is conservation. In professional communication it is important to distinguish terms applied in architectural conservation, especially in relation to those that are generallyand often used (renewal, rehabilitation). From the history of protection three basic concepts concerning (architectural) heritage can be identifies. In modern times they are increasingly the subject of international documents and international organisations, that have in times of globalisation become the managers of World heritage. The basic management and protection doctrine that is still being promoted and developed is so called ˝integral heritage protection˝.
Keywords: arhitekturna dediščina; cultural heritage; konservatorstvo; kulturna dediščina; prenova; stavbna dediščina